Regioselective Synthesis of 1, 3‐ and 1, 2‐Tocopheryl Glyceride Ethers of Carboxylic Acids. Issue 3 (11th December 2014) - Choi, Bo Seul; Choi, Jeongae; Bak, Seonyoung; Koo, Sangho
Abstract: A regioselective synthetic method with which to access 1, 3‐tocopheryl glyceride ethers2 of diverse carboxylic acids was developed through Bu4 NBr‐catalyzed ring‐opening of tocopheryl glycidyl ether1 . Steglich esterification of the 1, 3‐tocopheryl acetyl‐glyceride ether2a with various carboxylic acids, followed by selective deprotection of 3‐acetate by LiEt3 BH reduction at –78 °C constitutes a regioselective synthetic method of 1, 2‐tocopheryl glyceride ethers4 . An example of the differing self‐assembled behavior of phosphorylcholine derivatives6c and7c of 1, 3‐ and 1, 2‐tocopheryl stearoyl‐glyceride ethers in aqueous solution is also described. Abstract : Bu4 NBr‐catalyzed regioselective acidolysis of α‐tocopheryl glycidyl ether and selective reduction of acetate by LiEt3 BH at –78 °C allowed the regioselective preparation of 1, 3‐ and 1, 2‐tocopheryl glyceride ethers.